Faktor-faktor yang Memengaruhi Perilaku Judi Online pada Remaja: Narrative Literature Review - Ida Ayu Pringga Mayradevi; David Hizkia Tobing (Jurnal Psikologi Perseptual)
Online gambling is the act of wagering money or valuable items to gain profits in which the amount is uncertain. Recently, online gambling has become prevalent among young people, and in this context, adolescents are prone to engaging in activities which can be detrimental to themselves and other people by committing acts of indecency like thievery and selling valuable items that can belong to others. Online gambling also has several negative impacts on the lives of adolescents, including a decline in academic performance, emotional instability, poor relationships with others, and gambling disorders. This research aims to examine the factors influencing online gambling behavior in adolescents. The study utilizes a literature review method with a narrative review type. The articles were accessed through sources such as Google Scholar, PubMed, Springer, and Science Direct, with publication years ranging from 2013 - 2023. Based on the literature review findings, five major categories were identified, including factors originating from the individual, family, social environment, socio-economic, and internet features. This literature review is expected to provide readers with comprehensive information on the factors that lead adolescents to engage in online gambling behavior. Additionally, it aims to serve as a foundation for developing interventions to address this issue.